Histological evaluation of acute ischemic stroke thrombi may indicate the occurrence of vessel wall injury during mechanical thrombectomy. (11th May 2021) - Mereuta, Oana Madalina; Abbasi, Mehdi; Fitzgerald, Seán; Dai, Daying; Kadirvel, Ram; Hanel, Ricardo A; Yoo, Albert J; Almekhlafi, Mohammed A; Layton, Kennith F; Delgado Almandoz, Josser E; Kvamme, Peter; Mendes Pereira, Vitor; et al.
Abstract : Background: Several animal studies have demonstrated that mechanical thrombectomy (MT) for acute ischemic stroke (AIS) may cause vessel wall injury (VWI). However, the histological changes in human cerebral arteries following MT are difficult to determine. Objective: To investigate the occurrence of VWI during MT by histological and immunohistochemical evaluation of AIS clots. Methods: As part of the multicenter STRIP registry, 277 clots from 237 patients were analyzed using Martius Scarlett Blue stain and immunohistochemistry for CD34 (endothelial cells) and smooth muscle actin (smooth muscle cells). Results: MT devices used were aspiration catheters (100 cases), stentriever (101 cases), and both (36 cases). VWI was found in 33/277 clots (12%). There was no significant correlation between VWI and MT device. The degree of damage varied from grade I (mild intimal damage, 24 clots), to grade II (relevant intimal and subintimal damage, 3 clots), and III (severe injury, 6 clots). VWI clots contained significantly more erythrocytes (p=0.006*) and less platelets/other (p=0.005*) than non-VWI clots suggesting soft thrombus material. Thrombolysis correlated with a lower rate of VWI (p=0.04*). VWI cases showed a significantly higher number of passes (2 [1–4] vs 1 [1–3], p=0.028*) and poorer recanalization outcome (p=0.01*) than cases without VWI. Conclusions: Histological markers of VWI were present in 12% of AIS thrombi, suggesting that VWI might be related to MT. VWI was associated with soft thrombus consistency, higher number of passes and poorer revascularization outcome. There was no significant correlation between VWI and MT device.